Intrinsic Differences in Immune Checkpoint Inhibitor-Induced Myocarditis: A Retrospective Analysis of Real World Data - Lei, Yanna; Zheng, Xiufeng; Huang, Qian; Li, Xiaoying; Qiu, Meng; Liu, Ming (Frontiers in Pharmacology, 2022)
Immune-related myocarditis is a severe and even life-threatening immune-related adverse event (irAE) which may also be underestimated due to the challenge in diagnosis. There have been few reports about the intrinsic difference between patients with immune-associated myocarditis. A retrospective analysis was conducted between March 2019 to June 2020 in West China Hospital and 18 patients with immune-related myocarditis were studied. Cases were classified as mild (n=12) or severe myocarditis (n=6) according to the clinical manifestations and haemodynamic complications. Covariates extracted from medical records were compared in different groups, and factors associated with severe myocarditis were identified. In this retrospective analysis, the median age of the 18 patients was 60 years old. Most cases occur early and approximately after the first or second ICI infusion. The severity of myocarditis may be correlated with lactate dehydrogenase (LDH) (P=0.04) and troponin (P=0.0057). The relationship between troponin and myocarditis was further confirmed in another cohort which including 30 patients. In addition, patients are more likely to develop multi-irAEs, and myositis was the most common second irAE. Those who experience multi-irAEs had significantly higher LDH (P=0.02) as well as myoglobin levels (P=0.02) than did not experience. All patients were treated with steroids timely and the mortality rate was 5.6% in our study. In this study, we explore risk factors for severe myocarditis and we emphasized the importance of a multidisciplinary team in assisting diagnosis and treatment options. It is critical to initiate corticosteroid therapy, regardless of the severity of the myocarditis.